A Profile of CPA Candidates. - Williams, Doyle Z.; Mead, George C. (The Accounting Review, 1969)
Abstract The article discusses the profile of CPA candidates. It is important, for the accounting profession to evaluate periodically the characteristics of its recruits to determine if those who seek to enter its ranks are equipped with the attributes necessary to deal effectively with the increasingly complex problems of the profession. The public accounting profession has a common bridge over which all those seeking to enter its ranks must cross-the Uniform CPA Examination. Thus by examining the characteristics of CPA candidates, a profile can be drawn of the traits both of those who are seeking entrance into the profession of public accounting and those who are successful in doing so. Approximately one-half of the candidates writing the examination for the first time are under twenty-five years of age and are attending college or have been out of college for less than one year. If they have graduated from college, they likely are employed in public accounting with a CPA firm. The amount of formal course work in quantitative methods studied by CPA candidates is increasing. Experience does not contribute to the success of candidates on the CPA examination. Candidates should be encouraged to take the examination as near the time as they complete their course work in accounting as possible.